Nutrition practice during ultramarathon running in theory and reality - Choroszewicz, Paweł; Brzezinski, Łukasz; Dybowski, Maksymilian; Różański, Gracjan; Dobosiewicz, Anna; Zukow, Xawery (Journal of Education, Health and Sport, 2018)
The article presents the theory of nutrition during extreme efforts as are races on ultramarathon distances. It shortly depicts processes and mechanisms taking place in human body in order to replenish energy reserves needed to complete the race and presents theoretically optimal nutrition plan for a sample runner. It mentions potential health issues waiting for athletes hindering, and sometimes making it impossible to complete the run. Finally it compares the theory with reality, showing nutrition plans used by elite athletes during competitions.